Communication Strategies of Indonesian Secondary School Teachers to Establish Interpersonal Relationships with Students; A Literature Review - Pratama, Moch Johan; Mukhlis, Hamid (Utan Kayu Publishing, 2024)
The quality of teacher-student relationships has a profound impact on the learning process and outcomes, particularly in culturally diverse contexts like Indonesia. In Indonesian secondary schools, where cultural characteristics such as power distance and collectivism shape interactions, enhancing teacher-student relationships through effective communication strategies is crucial. This study aims to identify and analyze communication strategies that are most appropriate for fostering interpersonal relationships in Indonesian secondary schools. Using a qualitative literature review method, following PRISMA guidelines, this study synthesizes 22 communication behaviors from existing literature, which were categorized into four main themes: care, immediacy, clarity, and disclosure. Notably, while the strategies of care, immediacy, and clarity align with previous research and are adapted to the Indonesian cultural context, the study found a significant lack of teacher disclosure, a critical strategy for building close interpersonal relationships. This gap suggests that cultural factors such as high power distance may inhibit the use of disclosure as a relational tool in Indonesian classrooms. The study’s findings provide practical implications for teachers aiming to improve their communication practices, suggesting that culturally appropriate strategies, particularly in balancing authority and relational closeness, are necessary to foster stronger interpersonal connections with students.